2000
DOI: 10.1097/00000542-200006000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Inhibits NF-κB Nuclear Binding in Human Neutrophils and Monocytes by a Nitric Oxide–dependent Mechanism

Abstract: Morphine causes immunosuppression, at least in part, via the NO-stimulated depression of NF-kappaB nuclear binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 38 publications
4
64
0
7
Order By: Relevance
“…A variety of different stimuli, including cytokines, oxidative stress, apoptosis-inducing stimuli and drugs used in anticancer treatment, are able to activate NF-κB (20,21). Previous studies have demonstrated that morphine directly inhibits NF-κB function via the release of nitric oxide (NO) (22,23). Similarly, in the present study, fentanyl inhibited NF-κB expression in human gastric carcinoma cells.…”
Section: Discussionsupporting
confidence: 64%
“…A variety of different stimuli, including cytokines, oxidative stress, apoptosis-inducing stimuli and drugs used in anticancer treatment, are able to activate NF-κB (20,21). Previous studies have demonstrated that morphine directly inhibits NF-κB function via the release of nitric oxide (NO) (22,23). Similarly, in the present study, fentanyl inhibited NF-κB expression in human gastric carcinoma cells.…”
Section: Discussionsupporting
confidence: 64%
“…88 It has been demonstrated that high concentrations of NO can inhibit NF-kB activation in macrophage cell lines 91 and human macrophages, 120 monocytes 121 and neutrophils. 121,122 NO may inhibit NF-kB DNA binding through S-nitrosation of the p50 subunit of the transcription factor, as has been demon-strated in isolated NF-kB protein 123 and in human respiratory cells and murine macrophages. 124 Alternatively, transcriptional induction and stabilisation of the inhibitory molecule IkB, that keeps NF-kB sequestered in the cytoplasm, may account for the inhibition of NF-kB activity.…”
Section: Proapoptotic Mechanismsmentioning
confidence: 93%
“…Thus, a reduction in the production of these cytokines and mediators could affect the generation of a fever response. Interestingly, chronic opiate exposure has been shown to inhibit nuclear factor kappa B (NFκB) (e.g., Wang et al, 2005;Welters et al, 2000), a transcription factor involved in the downstream effects of IL-1β (Nadjar et al, 2003) and the production of PGE 2 (Pistritto et al, 1999). There is some precedent for effects downstream of IL-1 affecting fever responding following developmental insults.…”
Section: Discussionmentioning
confidence: 99%